Two are Few and Four are Many: Number Effects in Experimental Oligopolies - Steffen Huck; Hans-Theo Normann; Jörg Oechssler (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
In this paper we investigate how the competitiveness of Cournot markets varies with the number of firms in an industry. We review previous Cournot experiments in the literature. Additionally, we conduct a new series of experiments studying oligopolies with two, three, four, and five firms in a unified frame. With two firms we find some collusion. Three-firm oligopolies tend to produce outputs at the Nash level. Markets with four or five firms are never collusive and typically settle at or above the Cournot outcome. Some of those markets are actually quite competitive with outputs close to the Walrasian outcome.
Keywords: L13; C92; C72; 330; Cournot markets; oligopolies; experiments